A critical evaluation of promotional drug literatures available with prescribers at a tertiary care teaching hospital in Gujarat, India - Mistry, Vimesh R.; Kanani, Neeta J.; Thacker, Kuntal S. (International Journal of Basic & Clinical Pharmacology, 2022)
Background: Promotional literature provided by the pharmaceutical companies is one of the important marketing strategies to prescribe. Many of these literatures do not follow ethical guidelines and contain biased and irrelevant information that may cause irrational prescribing. So we did this study with an aim to check the credibility, reliability and authenticity of the PDLs available with prescribers. Methods: Promotional drug literatures were analyzed based on various parameters and guidelines provided by world health organization. Statistical analysis was done using Microsoft Excel. Results: A total 395 promotional drug literatures were analyzed and very few of them fulfilled the ethical criteria for drug promotion. Most of them focused on providing information about generic name, brand name manufacture company name and claims about efficacy. Few of them focused on safety of drugs as less information provided about adverse reaction, precaution and drug-drug interaction. Many of them contain space occupying unnecessary pictures. Conclusions: It can be concluded that the majority of the promotional advertisements that were given to the prescribers do not follow ethical guidelines and were not able to improve rational prescribing but only have commercial benefits.